Exploration of Sustainable Digital Marketing Approaches for Amplifying Micro, Small and Medium Enterprises Product Branding - Ekawahyu Kasih; Cahyatih Kumandang; Grace Yulianti (Proceeding of The International Conference on Economics and Business, 2022)
This study aims to explore sustainable digital marketing approaches for enhancing the branding of Micro, Small, and Medium Enterprises (MSMEs) products. The research model adopts a qualitative methodology to delve into the intricacies of digital marketing strategies utilized by MSMEs. Sampling techniques involve purposive sampling, focusing on MSMEs actively engaged in digital marketing practices. Data collection methods include in-depth interviews and content analysis of digital marketing materials. Through thematic analysis, the study examines the effectiveness and sustainability of various digital marketing approaches adopted by MSMEs. Findings highlight innovative strategies, such as social media marketing, content creation, and influencer collaborations, as pivotal in amplifying product branding for MSMEs. The research underscores the importance of sustainability in digital marketing endeavors for long-term brand growth and competitiveness in the contemporary marketplace.